Implementing a social innovation for community-based peer support for immigrant mothers in Sweden: a mixed-methods process evaluation - Kåks, Per; Stansert Katzen, Linnea; Målqvist, Mats; Bergström, Anna; Herzig van Wees, Sibylle (Frontiers in Public Health, 2024)
Introduction A South African social innovation based on peer support for mothers was contextualized in southern Sweden. The objective of the project was to support expectant women and mothers of young children in immigrant communities to access public services that would benefit maternal and child health. This study aimed to assess how the intervention was implemented, what the contextual barriers and facilitators were, and how the implementation was perceived by those who delivered and received it. Methods The study used mixed methods with a convergent parallel design and followed the Medical Research Council guidance on process evaluations of complex interventions. Semi-structured interviews (n=19) were conducted with peer supporters, client mothers, and key stakeholders involved in the intervention. The qualitative data were analyzed using content analysis. Quantitative data on peer supporters’ activities were collected during contacts with client mothers and were presented descriptively. Results The five peer supporters had 1,294 contacts with client mothers, of which 507 were first-time contacts. The reach was perceived as wide, and the dose of the intervention was tailored to individual needs. Barriers to implementation included community mistrust of social services, norms on gender roles and parenting, and funding challenges. The implementation was facilitated by the organization's reputation, network, experience, and third-sector affiliation. Peer supporters tended to prioritize linking clients to other services over the educational components of the intervention, sometimes doing more than what was originally planned. Implementation strategies used included building trust, using multiple outreach venues, using internal support structures, and providing practical assistance as an entry point to comprehensive psychosocial support. The personal connection between peer supporters and clients was highly valued, and the building of relationships enabled them to address sensitive topics. Peer supporters sometimes experienced a blurred line between professional and personal roles. Conclusions Peer supporters used a variety of strategies to navigate identified barriers and facilitators. Trust was central both as a contextual factor and a strategy for implementation. It is valuable to maintain a balance between flexibility and adherence to the function of peer supporters. Further research is needed to evaluate the effects of the intervention.